2013
DOI: 10.1002/bies.201300028
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and the evolutionary ecology of bacterial virulence: TheBacillus cereusgroup as a novel study system

Abstract: How significant is social evolution theory for the maintenance of virulence in natural populations? We assume that secreted, distantly acting virulence factors are highly likely to be cooperative public goods. Using this assumption, we discuss and critically assess the potential importance of social interactions for understanding the evolution, diversity and distribution of virulence in the Bacillus cereus group, a novel study system for microbial social biology. We conclude that dynamic equilibria in Cry toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 108 publications
(163 reference statements)
4
49
0
3
Order By: Relevance
“…These results are consistent with the highly related nature of the B. cereus, B. anthracis, and B. thuringiensis species (14,15,52). In addition to host range, superinfection studies were performed in order to assess whether the phages were strictly lytic or temperate.…”
Section: Resultssupporting
confidence: 76%
“…These results are consistent with the highly related nature of the B. cereus, B. anthracis, and B. thuringiensis species (14,15,52). In addition to host range, superinfection studies were performed in order to assess whether the phages were strictly lytic or temperate.…”
Section: Resultssupporting
confidence: 76%
“…In comparison with the the individual survival traits with few interactions and no compartmentalization (Manning and Kuehn, 2013), a different group of bacteria has emerged with survival strategies similar to the eukaryotes (Raymond and Bonsall, 2013; Spitzer and Poolman, 2013). With ordered structural organization, fine-tuned physiology, and interactive social behavior, a paradigm shift for better survival is observed in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The PlcR-PapR and NprR-NprX systems (Perchat et al, 2011) of LM1212 were found identical to those of the anthrax-casing B. cereus G9241, although it contained no anthrax toxin genes and did not produce a capsule. Broadly, strains in the anthrax clade are more likely to be associated with vertebrate hosts, whereas most entomopathogenic Bt strains fall into a different clade (Raymond and Bonsall, 2013b). The natural host affiliations of Bt strains in the anthrax clade are almost entirely unknown and so it was not surprising that we were unable to identify an invertebrate host.…”
Section: Discussionmentioning
confidence: 97%
“…These species names do not represent good monophyletic groups, so it is difficult to distinguish them using chromosomal genetic typing methods (Helgason et al, 2000;Vilas-Boas et al, 2007;Raymond et al, 2010a). However, phylogenetic analysis of strains characterized by multiple locus sequence typing suggests that closely related strains are likely to have similar ecology or host association (Guinebretière et al, 2010;Raymond et al, 2010b;Raymond and Bonsall, 2013a). In this study, we identified LM1212 as a strain of Bt, based on both genetic typing methods (Supplementary Figure S3; Supplementary Table S3) and phenotypic identification (Figures 1b and 2; Supplementary Figures S2A and B).…”
Section: Discussionmentioning
confidence: 99%